Targeting of beneficiaries in chemical fertilizer subsidy programs: State of knowledge and evidence gaps - Trachtman, Carly; Hill, Ruth Vargas (International Food Policy Research Institute, 2025)
Low and middle income countries have been facing mounting pressure from lenders and donors to eliminate or reform fertilizer subsidy programs, which can have distortionary market effects and negative environmental externalities. However, there is little systematic work understanding who these programs currently benefit both in theory and in practice, and hence who may be affected by policy reform. In this paper, we identify low and middle countries with active fertilizer subsidy programs, and characterize the targeting regime of each program based on both explicit and implicit criteria determining eligibility. Then in a selection of case studies, we explore which individuals are receiving subsidy benefits in practice. We find that while many fertilizer subsidy programs are meant to be universal, there are are additional implicit targeting criteria and/or informal targeting induced by supply shortfalls in many countries. Further, we find evidence that regardless of targeting regime, fertilizer subsidies are generally progressive, though this seems to be driven by the fact that the poor are often concentrated in the agricultural sector.